Treatment outcomes and associated factors for hospitalization of children treated for acute malnutrition under the OptiMA simplified protocol: a prospective observational cohort in rural Niger - Phelan, Kevin; Seri, Benjamin; Daures, Maguy; Yao, Cyrille; Alitanou, Rodrigue; Aly, Ahmad Ag Mohamed; Maidadji, Oumarou; Sanoussi, Atté; Mahamadou, Aboubacar; Cazes, Cécile; Moh, Raoul; Becquet, Renaud; et al. (Frontiers in Public Health, 2023)
Introduction Globally, access to treatment for severe and moderate acute malnutrition is very low, in part because different protocols and products are used in separate programs. New approaches, defining acute malnutrition (AM) as mid-upper arm circumference (MUAC) < 125 mm or oedema, are being investigated to compare effectiveness to current programs. Optimizing Malnutrition treatment (OptiMA) is one such strategy that treats AM with one product – ready-to-use therapeutic food, or RUTF – at reduced dosage as the child improves. Methods This study aimed to determine whether OptiMA achieved effectiveness benchmarks established in the Nigerien National Nutrition protocol. A prospective cohort study of children in the rural Mirriah district evaluated outcomes among children 6-59 months with uncomplicated AM treated under OptiMA. In a parallel, unconnected program in one of the two trial sites, all non-malnourished children 6-23 months of age were provided small quantity lipid-based nutritional supplements (SQ-LNS). A multivariate logistic regression identified factors associated with hospitalization. Results From July-December 2019, 1,105 children were included for analysis. Prior to treatment, 39.3% of children received SQ-LNS. Recovery, non-response, and mortality rates were 82.3%, 12.6%, and 0.7%, respectively, and the hospitalization rate was 15.1%. Children who received SQ-LNS before an episode of AM were 43% less likely to be hospitalized (ORa=0.57; 0.39-0.85, p = 0.004). Discussion OptiMA had acceptable recovery compared to the Nigerien reference but non-response was high. Children who received SQ-LNS before treatment under OptiMA were less likely to be hospitalized, showing potential health benefits of combining simplified treatment protocols with food-based prevention in an area with a high burden of malnutrition such as rural Niger.